1997
DOI: 10.1016/s0301-5629(96)00205-0
|View full text |Cite
|
Sign up to set email alerts
|

Phantoms and automated system for testing the resolution of ultrasound scanners

Abstract: Abstract-Tissue-mimicking phantoms and an automated system have been developed for testing the resolution performance of ultrasound scanners by determining detectability of low to higher contrast spherical lesions over the entire depth of field. Axial, lateral and elevational resolutions are accounted for simuRaneously and equally. Tissue-mimicking spherical simulated lesions are either 3 or 4 mm in diameter and have one of four different intrinsic material contrasts. For each diameter and contrast, there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…Recently, Rownd et al described a method for computerized assessment of ultrasound system performance: 8 In brief, they developed a very sophisticated technique for computing lesion signal to noise ratios in images of phantoms containing tissue-mimicking spherical lesions. A computer program they wrote automatically analyzes the ultrasound images to determine the depth ranges over which lesions of specific diameters and material contrasts are detected.…”
Section: Computerized Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Rownd et al described a method for computerized assessment of ultrasound system performance: 8 In brief, they developed a very sophisticated technique for computing lesion signal to noise ratios in images of phantoms containing tissue-mimicking spherical lesions. A computer program they wrote automatically analyzes the ultrasound images to determine the depth ranges over which lesions of specific diameters and material contrasts are detected.…”
Section: Computerized Image Analysismentioning
confidence: 99%
“…One difference for laser printers is instead of creating a test film with a sensitometer, one creates the test film by recording a digitized image of a known grayscale pattern such as the SMPTE pattern. 8 The pattern should be stored internally in the ultrasound unit.…”
Section: Film Sensitometrymentioning
confidence: 99%
“…Lateral resolution proved to be worse than axial resolution, especially in 3.5-MHz transducers, thus indicating the possible presence of various defects, most of all with regard to ultrasound beam focusing [8,11,[13][14][15][16]. This should be emphasised because it is precisely the lateral resolution more than the axial resolution that has an important impact on image quality.…”
Section: Discussionmentioning
confidence: 97%
“…It was Rownd et al [19] who first developed a test object and automated system to test axial, lateral, and transverse resolution. Kofler et al [20] thereafter showed there was agreement between automated analysis and radiologists on clinical image quality.…”
Section: Discussionmentioning
confidence: 99%